Spelling Bee Game Effect to Teach Vocabulary - Mukminatus Zuhriyah; Lailatur Rohmah (International Journal of English Education and Linguistics (IJoEEL), 2022)
This study aimed to test student vocabulary skills front and back class using the Spelling Bee game. A pre-experimental design was used. This research was conducted at Salafiyah Safi'iyah Seblak Diwek Jombang, MT. The sample for this study was class VII D students of MT Salafiya Safiya Sebrak Diwek Jomban for the 2021-2022 academic year. Researchers analyzed data using t-tests with SPSS V.25. After collecting the data, the researchers received results before and after the test, with a average pretest score of 65.68 for her and a mean post-test score of 77.05. The researchers then analyzed the data using a t-test, with a Sig. (two-tailed) result of less than 0.05. Ha can be said to have been accepted. Several conclusions were drawn based on the results of the data analysis. That is, students' vocabulary before teaching with the Spelling Bee Game appeared lower than it was after being taught with the Spelling Bee Game. Vocabulary of students before and after teaching with the spelling bee game. Therefore, maybe concluded and the spelling bee game is effective in class the vocabulary of class VII D of MT Salfiyah Safi`iyah Seblak Diwek Jombang.